Perfect Fluid Coupled String Universe in f(R,T) Gravity - Pawar, K.; Dabre, A. (Journal of Scientific Research, 2023)
In this paper, we have investigated the Bianchi type VI0 space-time in the presence of string of clouds coupled with perfect fluid within the context of f(R,T) gravity. The exact solutions to the field equations have been obtained by considering the expansion scalar Θ is proportional to the shear scalar σ and the exponential form of an average scale factor. Some physical and kinematical parameters of the constructed model have been discussed and presented graphically, and it is interesting to note that the resultant model resembles the recent observational data. Also, we have discussed the energy conditions for a perfect fluid-coupled string cosmological model.